Molecular distinctions between pediatric and adult mature B-cell non-Hodgkin lymphomas identified through genomic profiling - Deffenbacher, Karen E. (American Society of Hematology, 2012)
Burkitt lymphoma (BL) predominates in pediatric patients, whereas diffuse large B-cell lymphoma (DLBCL) is uncommon. In contrast to adults, BL and DLBCL are treated similarly in children and both entities have superior outcomes in children compared with adults. Gene expression profiling (GEP) and miRNA expression profiling clearly differentiated pediatric DLBCL from BL, forming distinct clusters regardless of patient age. However, pathway analysis of GEP data identified minor differences between corresponding pediatric and adult tumors. Predominance (6:1) of the germinal center B-cell subtype to activated B-cell subtype was found among pediatric DLBCL. Two cases were molecularly classified as primary mediastinal B-cell lymphoma. We observed frequent abnormalities in 8q24 in pediatric DLBCL, including MYC rearrangement in 31% (5 of 16) and gain or amplification in 50% (6 of 12) nonrearranged cases. MYC rearrangement was present in 96% (23 of 24) BL cases. Array-based CGH analysis identified abnormalities that are shared between adult and pediatric DLBCL (+12q15, +19q13, −6q), and abnormalities unique to the pediatric cases (−4p14, −19q13.32, +16p11.2), suggesting distinct pathogenetic mechanisms relative to age. Elucidation of the underlying target genes may provide insight into factors that modulate outcome and could provide potential novel therapeutic targets with less toxicity for pediatric patients with B-cell non-Hodgkin lymphoma.